A critical evaluation of Edward Said's literary critical concept in culture and imperialism - Alhomoud, Ghassan Nawaf Jaber (Research Journal in Advanced Humanities, 2024)
This study aims to assess the validity of Said's humanistic critique in establishing a comprehensive critical theory that integrates both theoretical and practical aspects. Thus, it clarifies the cognitive frameworks of Edward Said's concept of criticism through an analysis of his interpretation of culture. It clarifies how Said successfully applied the theoretical tenets of humanistic criticism by providing a comprehensive analysis of culture. Said's humanistic criticism transcends merely exposing the deficiencies of contemporary American critical theory, as demonstrated by its arcane professionalization. It aims to deconstruct professionalization, replacing it with critical values that associate critical theory with its context, allowing the intellectual to elucidate the disparities within the interrelated historical experiences. Transforming the frameworks of traditional criticism is both theoretical and practical. The theoretical aspects of Said's concept of criticism emphasize the literary tenets promoted by both classical and contemporary American criticism. Nevertheless, the practical aspects of Said's humanistic critique relate to the intellectual's capacity to transform Saidian theoretical concepts of humanistic criticism from theoretical boundaries to practical application. In other words, how Said could express cognitive frameworks that alter the established intellectual perspectives of his background and society into a more humane perspective, allowing him to reassess modern critical theory.